New compliance guidance by SEC staff signals increased scrutiny of non-GAAP financial measures. Issue 4 (7th November 2016) - Parrino, Richard J.
Abstract : Purpose: This article examines compliance and disclosure interpretations issued by the staff of the Securities and Exchange Commission in May 2016 that provide guidance to SEC-reporting companies on how they can use financial measures not prepared in accordance with generally accepted accounting principles in a manner that complies with SEC rules governing the presentation of non-GAAP measures in SEC filings and other public communications. Design/methodology/approach: This article provides an in-depth analysis of the new interpretive guidance in the context of the increasing use of non-GAAP financial measures by SEC-reporting companies and the SEC's concern that some companies have been using non-GAAP measures inappropriately to present a materially different picture of their operating performance than investors can discern from financial measures prepared in accordance with GAAP. Findings: Although the appropriate use of non-GAAP financial measures can enhance investor understanding of a company's business and operating results, a relatively permissive SEC attitude towards the use of non-GAAP measures in recent years has emboldened some companies to increase their reliance on non-GAAP measures in a manner the SEC views as inconsistent with its rules. The SEC staff's new guidance signals a renewed focus by the SEC on compliance with its requirements concerning the nature of permissible non-GAAP measures and the ways in which companies should present those measures. Originality/value: This article provides expert guidance on a major new SEC disclosure requirement from experienced securities lawyers.